Mathematics 2012 Study Mode

Try this quiz in CBT Mode
Mathematics 2012 in CBT Mode

Please share this quiz link to your friends, they might need it!

Quiz link
you can share this link with your friends
copy link veiw live

Join Discuss Share Question Share to WhatsApp
Question 11
A
-871 
B
-781 
C
-187 
D
-178 
Explanation.
Share Answer Hence f(x) = 2x3 - 11x2 + 8x - 1

f(-3) = 2(-3)3 - 11(-3)2 + 8(-3) - 1

= 2(-27) - 11(9) + 8(-3) - 1

= -54 - 99 - 24 - 1

= -178

Correct Option:
D

Join Discuss Share Question Share to WhatsApp
Question 12
A
x = 0, y = -2 
B
x = 0, y = 2 
C
x = 2, y = 0 
D
x = -2, y = 0 
Explanation.
Share Answer x2 - y2 = 4 .... (1)
x + y = 2 .... (2)

Simplify eqn (1)

(x + y)(x - y) = 4

From eqn (2)
x + y = 2 so substitute it into simplified eqn (1), we have

2 (x - y) = 4

therefore,
x - y = 2 ... (1)
x + y = 2
---------
2x = 4
---------

x = 2, when y = 0

Correct Option:
C

Join Discuss Share Question Share to WhatsApp
Question 13
A
\(\sqrt{17}\) 
B
\(\frac{4}{3}\) 
C
\(\frac{8}{3}\) 
D
\(\frac{2}{3}\) 
Explanation.
Share Answer y \(\alpha \sqrt{n}\)

y = k\(\sqrt{n}\)

when y = 4, n = 4
4 = k\(\sqrt{4}\)

4 = 2k

k = 2

Therefore,

y = 2\(\sqrt{n}\)

y = 2\(\sqrt{\frac{16}{9}}\)

y = 2\((\frac{4}{3})\)

y = \(\frac{8}{3}\)

Correct Option:
C

Join Discuss Share Question Share to WhatsApp
Question 14
A
24 
B
27 
C
32 
D
36 
Explanation.
Share Answer U \(\alpha \frac{1}{V^3}\)

U = \(\frac{k}{V^3}\)

k = UV3

k = 81 x 23 = 81 x 8

When V = 3,

U = \(\frac{k}{V^3}\)

U = \(\frac{81 \times 8}{3^3}\)

U = \(\frac{81 \times 8}{27}\) = 24

Correct Option:
A

Join Discuss Share Question Share to WhatsApp
Question 15
A
\(y > \frac{2}{3}\) 
B
\(y < \frac{2}{3}\) 
C
\(y > -\frac{2}{3}\) 
D
\(y < -\frac{2}{3}\) 
Explanation.
Share Answer \(\frac{1}{5}y + \frac{1}{5} < \frac{1}{2}y + \frac{2}{5}\)

Collect like terms

\(\frac{y}{5} - \frac{y}{2} < \frac{2}{5} - \frac{1}{5}\)

\(\frac{2y - 5y}{10} < \frac{2 - 1}{5}\)

\(\frac{-3y}{10} < \frac{1}{5}\)

\(y > \frac{-2}{3}\)

Correct Option:
C


Join Discuss Share Question Share to WhatsApp
Question 17
A
24 
B
23 
C
-24 
D
-25 
Explanation.
Share Answer n2 - 6n - 4

For the 3rd term,
32 - 6(3) - 4

9 - 18 -4 = -13

For the 4th term,
42 - 6(4) - 4

16 - 24 - 4 = -12

Sum of both terms

-13 - 12 = -25

Correct Option:
D

Join Discuss Share Question Share to WhatsApp
Question 18
A
\(-\frac{1}{5}\) 
B
\(-\frac{1}{4}\) 
C
\(-\frac{1}{3}\) 
D
\(-\frac{1}{2}\) 
Explanation.
Share Answer Sr = \(\frac{a}{1 - r}\)

\(-\frac{1}{10}\) = \(\frac{1}{8} \times \frac{1}{1 - r}\)

\(-\frac{1}{10}\) = \(\frac{1}{8(1 - r)}\)

\(-\frac{1}{10}\) = \(\frac{1}{8 - 8r}\)

cross multiply...

-1(8 - 8r) = -10

-8 + 8r = -10

8r = -2

r = -1/4

Correct Option:
B

Join Discuss Share Question Share to WhatsApp
Question 19
A
11 
B
13 
C
15 
D
22 
Explanation.
Share Answer p * q = pq + p - q

First execute for 3 * 4

==> 3(4) + 3 - 4 = 12 + 3 - 4 = 11

Now we execute for 2 * 11

==> 2(11) + 2 - 11 = 22 + 2 - 11 = 13

Correct Option:
B

Join Discuss Share Question Share to WhatsApp
Question 20
A
\(-\frac{4}{5}\) 
B
\(-\frac{2}{5}\) 
C
D
Explanation.
Share Answer m \(\propto\) n = \(\frac{mn}{2} - a\)

Identify = e = 2

a \(\propto\) a-1 = e

a \(\propto\) a-1 = 2

-5 \(\propto\) a-1 = 2

\(\frac{-5 \times a^{-1}}{2} = 2\)

\(a^{-1} = \frac{2 \times 2}{-5}\)

\(a^{-1} = -\frac{4}{5}\)

Correct Option:
A

Previous Page Next Page
Question Map